Defining new roles and competencies for administrative staff and faculty in the age of competency-based medical education. (3rd April 2023) - Yilmaz, Yusuf; Chan, Ming-Ka; Richardson, Denyse; Atkinson, Adelle; Bassilious, Ereny; Snell, Linda; Chan, Teresa M.; ,
Abstract: Purpose: These authors sought to define the new roles and competencies required of administrative staff and faculty in the age of CBME. Method: A modified Delphi process was used to define the new CBME roles and competencies needed by faculty and administrative staff. We invited international experts in CBME (volunteers from the ICBME Collaborative email list), as well as faculty members and trainees identified via social media to help us determine the new competencies required of faculty and administrative staff in the CBME era. Results: Thirteen new roles were identified. The faculty-specific roles were: National Leader/Facilitator in CBME; Institutional/University lead for CBME; Assessment Process & Systems Designer; Local CBME Leads; CBME-specific Faculty Developers or Trainers; Competence Committee Chair; Competence Committee Faculty Member; Faculty Academic Coach/Advisor or Support Person; Frontline Assessor; Frontline Coach. The staff-specific roles were: Information Technology Lead; CBME Analytics/Data Support; Competence Committee Administrative Assistant. Conclusions: The authors present a new set of faculty and staff roles that are relevant to the CBME context. While some of these new roles may be incorporated into existing roles, it may be prudent to examine how best to ensure that all of them are supported within all CBME contexts in some manner.